UNCOVERING THE POTENTIAL OF UNDERDEVELOPED REGIONSSTUDY CASE: BELU REGENCY - Ni Putu Rekha Puspita (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The potential of underdeveloped regions is often overlooked, even though these regions hold “significant capital” that can encourage sustainable development. East Nusa Tenggara is one of the provinces in Indonesia that categorized as a under developed region, with Belu Regency having the lowest Village Development Index (IDM). This research aims to explore and identify the potential inherent in underdeveloped regions that has not been optimized. This research uses the Location Quotient (LQ) analysis method to identify base sectors, Shift Share (SSA) to measure economic growth, and Klassen Typology to classify regional growth patterns in Belu Regency. Novelty that can be provided in this research is the synergy of analysis that allows more precise diagnosis of problems and formulation of more targeted interventions. The result of the analysis show that the agriculture, forestry, and fisheries sectors; wholesale and retail trade, repair of cars and motorcycles; financial services; and real estate are the leading potential sectors that can be developed in the development of Belu Regency.